2020
DOI: 10.1029/2019gl086187
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Seismic Bathymetry Beneath Ekström Ice Shelf, Antarctica: Implications for Glacial History and Ice‐Ocean Interaction

Abstract: The shape of ice shelf cavities are a major source of uncertainty in understanding ice-ocean interactions. This limits assessments of the response of the Antarctic ice sheets to climate change. Here we use vibroseis seismic reflection surveys to map the bathymetry beneath the Ekström Ice Shelf, Dronning Maud Land. The new bathymetry reveals an inland-sloping trough, reaching depths of 1,100 m below sea level, near the current grounding line, which we attribute to erosion by palaeo-ice streams. The trough does … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…However, the fast-ice thickness still increases in spring and even during austral summer months (albeit very slowly). This can be explained by the measurement uncertainty with respect to the large spatial variability of sea-ice thickness even on very small (centimeter) scales, but the consistency in the data suggests that it could also be caused by consolidation processes within the platelet layer below, i.e., in situ sea-ice growth by heat transport into a supercooled plume residing right beneath the solid fast ice similar to observations in McMurdo Sound (Smith et al, 2012;Leonard et al, 2011;Dempsey et al, 2010;Robinson et al, 2014). So far, in Atka Bay there is only evidence that platelets grow quite large already while still suspended in the water column (Hoppmann et al, 2015b).…”
Section: Seasonal and Interannual Variability Of Snow Depth And Sea-imentioning
confidence: 55%
See 2 more Smart Citations
“…However, the fast-ice thickness still increases in spring and even during austral summer months (albeit very slowly). This can be explained by the measurement uncertainty with respect to the large spatial variability of sea-ice thickness even on very small (centimeter) scales, but the consistency in the data suggests that it could also be caused by consolidation processes within the platelet layer below, i.e., in situ sea-ice growth by heat transport into a supercooled plume residing right beneath the solid fast ice similar to observations in McMurdo Sound (Smith et al, 2012;Leonard et al, 2011;Dempsey et al, 2010;Robinson et al, 2014). So far, in Atka Bay there is only evidence that platelets grow quite large already while still suspended in the water column (Hoppmann et al, 2015b).…”
Section: Seasonal and Interannual Variability Of Snow Depth And Sea-imentioning
confidence: 55%
“…In that respect, Hoppmann et al (2015b) used a subset of oceanographic data collected by the nearby PALAOA hydrographic observatory (Boebel et al, 2006) to link fast-ice observations to ocean properties. A more recent study by Smith et al (2020) helped to constrain the boundary conditions for Ice Shelf Water outflow by mapping in great detail the cavity geometry of the Ekström Ice Shelf. This study also shows data from repeated CTD casts through a borehole in the ice shelf, revealing the buoyant outflow of Ice Shelf Water (ISW) in a relatively shallow surface layer.…”
Section: Spatial Variability Of Fast-ice Properties Related Tomentioning
confidence: 99%
See 1 more Smart Citation
“…Both projects collected coincident gravity, magnetic, and radio echo sounding (RES) data ( Figure 1b). Seismic data are incorporated for Ekström (Smith et al, 2020) and Fimbul ice shelves (Nøst, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…The ice shelf has passive shelf ice extending from the calving front to the middle of the ice shelf and is supported by the two promontories that buttress the shelf upstream. The bathymetry underneath has a deep inland-sloping trough reaching 1100 m below sea level near the current grounding zone (Smith and others, 2020). This trough extends from the calving front to the grounding zone, but oceanographic measurements from the same study, performed in the shallow regions of the ice shelf cavity showed no signs of warm sea water in the trough.…”
Section: The Dml and Enderby Land Coastsmentioning
confidence: 99%